How do students implement collaborative testing in real-world contexts?. Issue 2 (7th February 2016) - Wissman, Kathryn T.; Rawson, Katherine A.
Abstract : Recent research has explored the effects of collaborative testing, showing costs and benefits during learning and for subsequent memory. However, no prior research is informative about whether and how students use collaborative testing in real-world contexts. Accordingly, the primary purpose of the current research was to explore the extent to which students use collaborative testing during self-regulated learning. We conducted three surveys ( n = 692 across three samples) asking students about their use of collaborative testing, with a particular interest in conditions under which students report implementing collaborative testing. Among the key outcomes, a majority of students reported using collaborative testing when studying in a group. Additionally, students reported that key term definitions are the material most often used during collaborative testing. Students are also more motivated to use testing and believe testing is more effective and more fun when implemented in a group versus alone. Outcomes also shed light on metacognitive components of collaborative testing, with the student asking (versus answering) the question making the monitoring judgement whereas both students make the control decision about when to terminate practice. We discuss ways in which the collaborative memory literature can be extended to support more successful student learning.